Temperature‐dependent autoimmunity mediated by chs1 requires its neighboring TNL gene SOC3. Issue 3 (4th October 2016) - Zhang, Yao; Wang, Yuancong; Liu, Jingyan; Ding, Yanglin; Wang, Shanshan; Zhang, Xiaoyan; Liu, Yule; Yang, Shuhua
Summary: Toll/interleukin receptor (TIR)‐nucleotide binding site (NB)‐type (TN) proteins are encoded by a family of 21 genes in the Arabidopsis genome. Previous studies have shown that a mutation in the TN gene CHS1 activates the activation of defense responses at low temperatures. However, the underlying molecular mechanism remains unknown. To genetically dissect chs1‐mediated signaling, we isolated genetic suppressors of chs1‐2 ( soc ). Several independent soc mutants carried mutations in the same TIR‐NB‐leucine‐rich repeat (LRR) (TNL)‐encoding gene SOC3, which is adjacent to CHS1 on chromosome 1. Expression of SOC3 was upregulated in the chs1‐2 mutant. Mutations in six soc3 alleles and downregulation of SOC3 by an artificial microRNA construct fully rescued the chilling sensitivity and defense defects of chs1‐2 . Biochemical studies showed that CHS1 interacted with the NB and LRR domains of SOC3; however, mutated chs1 interacted with the TIR, NB and LRR domains of SOC3 in vitro and in vivo . This study reveals that the TN protein CHS1 interacts with the TNL protein SOC3 to modulate temperature‐dependent autoimmunity.